The integration of intercultural communicative competence in ELT settings: A systematic review - Permatasari, Indah (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
Intercultural communicative competence, commonly known as ICC, refers to the ability to respectfully compare and mediate between different cultural values. This study aims to systematically review the current trends and main findings of the studies focusing on the integration of ICC in ELT settings. A total of 17 peer-reviewed articles published between 2018 and 2022 were analysed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) items. The results showed that there has been a fluctuation in the number of studies published during the last four years. From the reviewed articles, it was found that most of the studies were conducted in Asia and used a qualitative method in examining the higher education students' skills and perspectives on ICC. Additionally, it was reported that using intercultural teaching and learning practices was effective in improving the participants' ICC. Nonetheless, many studies found it difficult to implement intercultural teaching and learning practices, particularly when it came to time constraints, learning material availability, and establishing success criteria. This underlines the necessity of creating a comprehensive instructional learning model that can help ESL and EFL teachers, as well as other educational practitioners, integrate ICC.